At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

What is the solution to this equation?

[tex]\[ 6(x-3) = 3x + 9 \][/tex]

A. [tex]\( x = -3 \)[/tex]
B. [tex]\( x = -1 \)[/tex]
C. [tex]\( x = 9 \)[/tex]
D. [tex]\( x = 3 \)[/tex]


Sagot :

Let's solve the equation step-by-step.

Given equation:
[tex]\[ 6(x - 3) = 3x + 9 \][/tex]

First, distribute the 6 on the left side of the equation:
[tex]\[ 6 \cdot (x - 3) = 6x - 18 \][/tex]

Now the equation becomes:
[tex]\[ 6x - 18 = 3x + 9 \][/tex]

Next, we move the [tex]\(3x\)[/tex] from the right side to the left side by subtracting [tex]\(3x\)[/tex] from both sides:
[tex]\[ 6x - 3x - 18 = 9 \][/tex]

Simplify the equation:
[tex]\[ 3x - 18 = 9 \][/tex]

Now, we move the [tex]\(-18\)[/tex] from the left side to the right side by adding 18 to both sides:
[tex]\[ 3x = 9 + 18 \][/tex]

Simplify the right side:
[tex]\[ 3x = 27 \][/tex]

Finally, we divide both sides by 3 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{27}{3} \][/tex]

Simplify:
[tex]\[ x = 9 \][/tex]

Therefore, the solution to the equation is:
[tex]\[ \boxed{x = 9} \][/tex]

So, the correct answer is:
[tex]\[ C. \ x = 9 \][/tex]